Train trip - Caswell, Deanna; Andreasen, Dan (New York : Disney/Hyperion Books, 2011)
While on a trip to visit his grandmother, a young boy enjoys the many sights and sounds he experiences along the way.
Keywords: Railroad trains -- Fiction; Voyages and travels -- Fiction; Stories in rhyme